Malociklična nosilnost pri ležajih z utrjeno kotalno površino - Kunc, Robert (Kovine zlitine tehnologije, 1998)
The paper deals with the problem of the actual carrying capacity of a rolling contact in large axial bearings with surface hardened raceway. The carying capacity of such bearings is usually given with the maximal permissible force on the rolling element with the highest load. The established criteria of maximal permissible plastic deformation of the raceway, and the maximal alowed subsurface stress on the hardened layer boundary give widely varrying values for the carrying capacity of the rolling contacts. In order to determine the actual carrying capacity of the rolling contact in axial bearings with low speed of rotation, considering base material properties, hardness and thickness of the hardened layer, and the geometry of the contact, we have measured the models of bearing raceways made of 42CrMo4 and C45 materials. The loads were static and low cycle dynamic. We have determined the cyclic curves (force-deformation), limit of fast increase in (elastic and plastic) deformation gradient, and the size of the contact surface. Simultaneously with the experiment, we have checked the subsurface stresses using FEM model, considering the material nonlinearities. On the basis of the measurement results and the FEM model we would like to set up a simplified mathematical relation that gives the permissible contact force considering the base and hardened material properties, and geometric model of the rolling contact.
Keywords: strojni elementi; kotalni ležaji; trenje; materiali; nosilnost; mehanske lastnosti